Modulation of Nrf2 by Activation of Estrogen Receptor β as a Therapeutic Strategy to Prevent Cancer Development and Overcome Inflammation-Related Drug Resistance in Breast Cancer - Emdormi Rymbai; Deepa Sugumar; Jubie Selvaraj; Ram Kothandam; Divakar Selvaraj (Tabriz University of Medical Sciences, 2023)
Despite the tremendous progress in breast cancer diagnosis and treatment, the mortality rate is expected to increase due to the emergence of drug resistance. Pro-inflammatory markers are thought to contribute to drug resistance by activation of its naive receptors and its downstream signaling pathways. Elevation of pro-inflammatory markers leads to an increase in the biosynthesis of estrogen which can promote the proliferation of estrogen receptor (ER)+ breast cancer. Inflammation also results in obesity which is one of the key risk factors. Estrogen receptor-beta (ER-β) is an important target that has been widely studied and accepted to possess anti-cancer activity in a number of cancers including breast cancer. ER-β elicits its action through genomic and non-genomic pathways. The genomic pathway increases the transcription of potent cyclin-dependent kinase inhibitor (p21), and tumor suppressor genes such as melanoma differentiation associated gene 7 and tumor protein (p53). The non-genomic pathway works through protein-protein interaction and phosphorylation. Here, we propose that the activation of ER-β might enhance the activation of nuclear factor-erythroid factor 2-related factor 2 (Nrf2) via estrogen receptor-alpha (ER-α) repression. The activation of Nrf2 increases the transcription of antioxidant genes such as NADH quinone oxidoreductase 1 (NQO1), heme oxygenase-1 (HO-1), etc., and decreases the expression of pro-inflammatory genes such as tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), etc. This review hypothesizes and suggests that ER-β agonists could play a beneficial role to overcome inflammation-related drug resistance by modulation of the Nrf2/antioxidant response element (Nrf2/ARE) pathway.